On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.